2014
DOI: 10.5713/ajas.2014.14258
|View full text |Cite
|
Sign up to set email alerts
|

A Whole Genome Association Study on Meat Palatability in Hanwoo

Abstract: A whole genome association (WGA) study was carried out to find quantitative trait loci (QTL) for sensory evaluation traits in Hanwoo. Carcass samples of 250 Hanwoo steers were collected from National Agricultural Cooperative Livestock Research Institute, Ansung, Gyeonggi province, Korea, between 2011 and 2012 and genotyped with the Affymetrix Bovine Axiom Array 640K single nucleotide polymorphism (SNP) chip. Among the SNPs in the chip, a total of 322,160 SNPs were chosen after quality control tests. After adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A genome-wide association study (GWAS) was performed using a mixed linear model implemented in GCTA v.1.91.4 beta3 [39]. Farm (1419), birth year (2006-2016), birth month (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), slaughter year (2008-2018), slaughter month (1-12), age (17-62 months), slaughter place (53), sire (324), and dam (8331) were tested for fixed effects. Fixed effects that were significant for all the traits were fitted in the model; this included farm, birth year, slaughter year, slaughter place, age, and sire.…”
Section: Genome-wide Association Analysis Heritability and Variancementioning
confidence: 99%
See 1 more Smart Citation
“…A genome-wide association study (GWAS) was performed using a mixed linear model implemented in GCTA v.1.91.4 beta3 [39]. Farm (1419), birth year (2006-2016), birth month (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), slaughter year (2008-2018), slaughter month (1-12), age (17-62 months), slaughter place (53), sire (324), and dam (8331) were tested for fixed effects. Fixed effects that were significant for all the traits were fitted in the model; this included farm, birth year, slaughter year, slaughter place, age, and sire.…”
Section: Genome-wide Association Analysis Heritability and Variancementioning
confidence: 99%
“…A genome-wide association study (GWAS) is an affordable and powerful tool to discover candidate genes and loci associated with quantitative traits [7]. GWASs in livestock, including in Hanwoo [8][9][10][11], have resulted in remarkable insights into the genetic architecture of carcass traits. Genetic variation in complex traits such as carcass and meat quality traits are, however, due to the contribution of many mutations with small effects [1,12] (polygenic effect).…”
mentioning
confidence: 99%
“…To meet the consumers’ demands, the selection of the Hanwoo breed has been focused on individuals with high intramuscular fat content (Lee et al, 2014). Few GWAS studies have been reported in Hanwoo cattle for traits like marbling, meat quality and sensory traits (Lee et al, 2010; Kim et al, 2011; Hyeong et al, 2014); however, no studies have examined the meat quality traits such as fat color, meat color and meat texture. Similarly, there is no published study, which uses imputed WGS data for these meat quality traits.…”
Section: Introductionmentioning
confidence: 99%
“…Some GWAS studies have been performed in Korean Hanwoo cattle 30 , Korean beef cattle 31 , and Australian taurine and indicine cattle 4 to detect SNPs associated with carcass and meat quantity traits. However, none of these reports focused on pathways in beef cattle.…”
mentioning
confidence: 99%